The Effect of Corn Ensiling Methods on Digestibility and Biogas Yield - Karol Kupryaniuk; Kamil Witaszek; Iryna Vaskina; Sebastian Filipek-Kaźmierczak; Jakub Kupryaniuk; Piotr Sołowiej; Jacek Dach (Energies)
This study investigates the impact of different corn silage preparation methods, namely the traditional and Shredlage methods, on digestibility and biogas yield in anaerobic digestion and its nutritional value—the first complex study of its kind. Key parameters of both silage types were analyzed, including chemical composition, fiber content, and elemental makeup. Methane and biogas production were assessed under standardized fermentation conditions. The results showed that the Shredlage method, characterized by more intensive chopping, led to higher biogas and methane yields per unit of organic dry matter compared to traditional silage. This improvement is attributed to enhanced digestibility due to the lower content of neutral detergent fiber (NDF), acid detergent fiber (ADF), and crude fiber in Shredlage. An elemental analysis revealed slight differences in carbon-to-nitrogen (C/N) ratios, with both silages showing values suitable for efficient fermentation. Despite minor variations in mineral content, Shredlage demonstrated greater efficiency in biogas production, particularly for rapid fermentation processes. The findings underscore the importance of silage preparation techniques in optimizing biogas yield and suggest Shredlage as a superior option for enhancing energy recovery in biogas plants. Future work should explore the economic trade-offs and scalability of these methods.